2014
DOI: 10.1080/13669877.2014.940597
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of risk behaviour: effects of perceived risks and risk attitude on farmer’s adoption of risk management strategies

Abstract: The importance of risk perception and risk attitude for understanding individual's risk behaviour are independently well described in literature, but rarely combined in an integrated approach. In this study, we propose a model assuming the choice to implement certain risk management strategies to be directly driven by both perceptions of risks and risk attitude. Other determinants influence the intention to apply different risk strategies mainly indirectly, mediated by risk perception and risk attitude. This c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
130
4
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(170 citation statements)
references
References 64 publications
9
130
4
4
Order By: Relevance
“…In order to determine the role of risk aversion on life satisfaction, we developed a psychometric scale reflecting risk attitudes, based on a number of attitudinal statements reflecting the importance of general farming related risks. The statements draw on a variety of previous work (see Bard and Barry, ; Pennings and Garcia, ; Xu et al ., ; Winsen et al ., ) and are designed to assess farmers’ attitudes towards general farming related risks. Factor analysis is used to reduce these data to a latent construct reflecting farmers’ degree of risk aversion.…”
Section: Risk Attitudesmentioning
confidence: 99%
“…In order to determine the role of risk aversion on life satisfaction, we developed a psychometric scale reflecting risk attitudes, based on a number of attitudinal statements reflecting the importance of general farming related risks. The statements draw on a variety of previous work (see Bard and Barry, ; Pennings and Garcia, ; Xu et al ., ; Winsen et al ., ) and are designed to assess farmers’ attitudes towards general farming related risks. Factor analysis is used to reduce these data to a latent construct reflecting farmers’ degree of risk aversion.…”
Section: Risk Attitudesmentioning
confidence: 99%
“…Veterinarians play a major role as key informants on the BS for cattle holders; indeed, they consider their veterinary practitioner as the main source of information and adopt BSM based on veterinary advices (Gunn, Heffernan, Hall, McLeod, & Hovi, ; Heffernan, Nielsen, Thomson, & Gunn, ; Sayers et al., ). On the other hand, veterinarians also represent an important risk factor in terms of disease spread, as many studies have listed visitors, and more specifically professional visitors such as veterinarians, as a key risk factor in terms of bio‐exclusion (Anderson, ; Brennan & Christley, ; Canadian Food Inspection Agency, ; Maunsell & Donovan, ; Mee, Geraghty, O'Neill, & More, ; NADIS, ; Nöremark, Frössling, & Lewerin, ; Sayers et al., ; van Schaik et al., ; van Winsen et al., ). Meanwhile, an ongoing survey implemented in Belgian cattle farms (unpublished data) confirmed that most cattle holders were not feeling comfortable in asking their veterinarians to wear clean and/or specific work clothes or boots when visiting their premises; they prefer relying on their professionalism in that regard.…”
Section: Introductionmentioning
confidence: 99%
“…Such selection criterion limits the representativeness, as the included farms are more likely to have improved their BS levels to eradicate the disease. In addition, only a few studies investigated the reasons why cattle farmers do not implement BSM (Brennan & Christley, ; Gunn et al., ; Heffernan, Nielsen, Thomson, & Gunn, ; Hoe & Ruegg, ; Ritter et al., ; Toma et al., ; van Winsen et al., ). The present study was more representative for all Belgian cattle farms and investigated the reasons of non‐implementation, which are key elements to better understand the farmers’ decision‐making process and the constraints to address in order to effectively improve BS level of cattle farms.…”
Section: Discussionmentioning
confidence: 99%